Trends and differences in the rates of autopsy in the United States, 2003 to 2020: A nationwide analysis - Dean M. Nelson, BBiomed, MD; Stephanie J. Rowe, BBiomed, MD; Adam Trytell, MBBS (Hons); Louise Fahy, MB BCh, BAO; Kelila Freedman, MSc; Andreas Pflaumer, MD, FHRS; Dion Stub, MBBS, PhD; Andre La Gerche, MBBS, PhD; Elizabeth D. Paratz, MBBS, PhD (Heart Rhythm O2)
Background: Autopsy, the gold standard for determining the cause of death, is declining globally. Significant differences exist between clinical diagnoses and those revealed at autopsy. Evidence of disparities in autopsy rates between different patient groups has previously been reported. Objective: To describe contemporary trends and disparities in autopsy rates according to sex, race, and urbanization, with particular attention to patients who have died because of cardiovascular disease (CVD). Methods: We accessed the Center for Disease Control Wide-Ranging Online Data for Epidemiological Research “Underlying Cause of Death” dataset for 2003 to 2020, to assess trends in autopsy rates in all-comers and for different subgroups stratified by sex, race, and degree of urbanization. Further primary and subgroup analysis was performed independently by the International Classification of Diseases, Tenth Revision cause of death criteria by chapter, subchapter, and specific diseases of interest. Linear regression was used to assess trends over time, with a significant coefficient considered evidence of temporal trend. Results: Annual autopsy rates decreased across the time period in all-comers, with an average autopsy rate of 3.66% (P < .001); however, this relationship was not demonstrated in CVDs. Men undergo autopsy more frequently than women, though autopsy rates in women with CVD are increasing (P = .011). Patients of non-White ethnicity and in metropolitan areas undergo autopsy at higher rates. Increasing autopsy rates are seen in ischemic heart disease (P < .001). Conclusion: Autopsy is decreasing in the United States; however, trends differ depending on patient factors (sex, ethnicity), social factors (degree of urbanization), and disease factors.